Os valores da economia solidária e os valores do trabalho: um estudo em empreendimentos econômicos solidários - Ana Carolina Guerra (2014)
This thesis aims to identify the values assigned to work and solidarity economy by members of solidary economic enterprises and their possible relationships. From the literature review the values assigned to construct Solidarity Economy was defined and put this to the test in a construct inseparably theoretical and empirical research. The concept of work values defined by Porto and Tamayo (2003) was also used. The sample used in the investigation of 174 members of 12 solidary economic enterprises in southern Minas Gerais. In the data analysis descriptive statistics, factor analysis, analysis of structure similarities (SSA), bivariate correlation and cluster analysis were used. From the analysis of the data values for different configurations of groups of participants were identified. It was evident that there is a great diversity of values and ideological principles within the solidary economic enterprises. The evidence of these values, and hence the high level of agreement presented by most respondents, reaffirms largely theoretical assumptions about the Solidarity Economy. Other results that need to be highlighted in this thesis, refers to the correlations found between the values of the Solidarity Economy and Work Values. In most cases, the correlations were significant, reaffirming the concept of Solidarity Economy as a way of organizing work. In this context, it can be said that the Solidarity Economy is a historic, albeit fragile and inchoate reality in many aspects of their development. However, despite its limitations, it is a reality, with great potential for economic, social and political development, in order to improve the quality of life and reduce social inequality. Thus, it is important to note, that the proposal of the Solidarity Economy, and consequently the exercise of rethinking the management, is not presented as an illusory proposal, utopian or naive, but a proposal that takes into account a way of organizing work, management, which is anchored in values associated with the search for a more egalitarian society.